Use of V-Go(®) Insulin Delivery Device in Patients with Sub-optimally Controlled Diabetes Mellitus: A Retrospective Analysis from a Large Specialized Diabetes System - Lajara, Rosemarie (Diabetes Ther, 2015)
INTRODUCTION: Tight glycemic control and timely treatment can improve outcomes in patients with diabetes yet many remain sub-optimally controlled. The objective of the current study was to evaluate the effect of switching patients with sub-optimally controlled diabetes to the V-Go(®) (Valeritas Inc., Bridgewater, NJ, USA) Disposable Insulin Delivery device. METHODS: A retrospective analysis of electronic medical records was conducted to assess patients with sub-optimal glycemic control defined as a glycated hemoglobin (HbA1c) >7%, switched to V-Go. Blood glucose control defined as change from baseline in HbA1c, prescribed insulin doses, body weight, concomitant anti-hyperglycemic agents, and reported hypoglycemia were collected prior to switching to V-Go and during V-Go use. RESULTS: Two-hundred and four patients were evaluated during the study period. Overall, there was a significant decrease in HbA1c after switching to V-Go at the 14- and 27-week follow-up visits. The least-squares mean (LSM) change in HbA1c (95% confidence interval) from baseline to 14 weeks was −1.53% (−1.69% to −1.37%; P < 0.001), and from baseline to 27 weeks was −1.79% (−1.97% to −1.61%; P < 0.001). Significant reductions in mean HbA1c were achieved at both visits in all patient subsets: Patients with type 2 and type 1/latent autoimmune diabetes in adults (LADA); patients using insulin at baseline and patients naïve to insulin at baseline. Patients administering insulin at baseline required significantly less insulin on V-Go (86–99 LSM units/day at baseline to 58 LSM units/day at 27 weeks; P < 0.001). Across all patients, reported hypoglycemic events were no more frequent on V-Go than on previous therapy. CONCLUSION: V-Go is safe and effective in patients with sub-optimally controlled diabetes requiring insulin therapy. Glycemic control improved significantly, less insulin was required, and hypoglycemic events were similar after patients switched to insulin delivery by V-Go. FUNDING: Valeritas, Inc. ELECTRONIC SUPPLEMENTARY MATERIAL: The online version of this article (doi:10.1007/s13300-015-0138-7) contains supplementary material, which is available to authorized users.